HEALTH IS THE MOST ESSENTIAL THING IN SURVIVAL AND THE CHOICE IS DETERMINED BY EACH INDIVIDUAL - Maitri Kalyani; Bernard T. Widjaja; Wani Devita Gunardi (RADJA PUBLIKA, 2023)
The necessities of human life include shelter, clothing and food. If the needs have been met, then human life can be said to be prosperous, but nevertheless, the need for health is the most essential thing in continuing the process of life. However, a clinical facility that has an idle capacity of 140 people with only 21% of visits if left unchecked will worsen the clinic situation. The purpose of this study was to determine the magnitude of the influence of service quality and location of the Ahmad Yani Lanumad Clinic on the selection of clinics mediated by brand image at the Semarang Army Aviation Education Center. The method in this study used quantitative descriptive analysis, with 125 respondents. Data collection was carried out by distributing questionnaires face-to-face and analyzed with the Warps application and SmartPLS 4.0. Conclusions obtained in this study Service quality has a significant effect on clinic selection but not clinic location if not mediated by brand image .